Bendopnea as an independent prognostic marker for adverse events in hospitalized heart failure patients: insights from a multicenter prospective cohort study - Wu, Yang; Zhu, Yuanting; Liu, Shuaiye; Hu, Yanqing; Ma, Shan (Frontiers in Cardiovascular Medicine, 2025)
Heart failure (HF) remains a leading cause of cardiovascular morbidity and mortality globally, affecting over 64 million individuals ( 1). Despite advancements in therapeutic strategies, the heterogeneity of HF symptoms complicates risk stratification and personalized management. Bendopnea, defined as dyspnea occurring within 30 s of forward trunk flexion, has emerged as a potential marker of hemodynamic compromise, yet its clinical significance in large multicenter cohorts remains underexplored. This prospective study enrolled 482 hospitalized HF patients from 2 tertiary care centers, stratifying them into bendopnea (n = 208) and non-bendopnea (n = 274) groups. Our results demonstrated that bendopnea was associated with more severe cardiac dysfunction, including lower left ventricular ejection fraction (LVEF: 38.9% ± 7.6% vs. 42.7% ± 8.1%, P < 0.001), larger left ventricular end-diastolic diameter (LVEDD: 63.8 ± 5.9 mm vs. 59.2 ± 5.6 mm, P < 0.001), and higher NT-proBNP levels (median 1,320.5 ng/L vs. 985.2 ng/L, P < 0.001). Over 1.5 years of follow-up, patients with bendopnea exhibited a significantly higher cumulative incidence of adverse events: HF rehospitalization (35.1% vs. 22.3%, P < 0.001), all-cause mortality (19.7% vs. 12.4%, P = 0.003), and arrhythmias requiring intervention (20.7% vs. 11.7%, P = 0.001). Multivariable Cox regression confirmed bendopnea as an independent predictor of adverse outcomes (HR = 1.6, 95% CI 1.3–2.0, P < 0.001). These findings highlight bendopnea as a clinically actionable marker for risk stratification in HF, supporting its integration into routine clinical practice.